Analisis Cultural Illiteracy pada Generasi Muda Akibat Lemahnya Pendidikan Kebudayaan di Indonesia - Corree Nathalia Tarigan; Sujarwo Sujarwo; Desy Safitri (Rayhan Intermedia, 2026)
Cultural Illiteracy is a condition where there is a lack of public understanding related to the diversity of traditions, values, norms, and cultural identity of the nation. This phenomenon of cultural illiteracy is one of the challenges for the younger generation in the midst of the development of digital technology and globalization trends. The younger generation tends to understand popular foreign cultures compared to local cultures, such as regional languages, cultural customs or traditions, traditional arts, and cultural values of the archipelago. This condition shows that cultural education in Indonesia is still not running optimally. This study aims to analyze cultural illiteracy in the younger generation due to the weak cultural education in Indonesia. The method used is a literature study, namely by examining relevant sources. The results of the study show that cultural illiteracy in Indonesia is characterized by the lack of knowledge of the younger generation about culture due to the lack of learning and implementation of culture in formal education. Thus, cultural education needs to be improved so that the younger generation is able to understand, and preserve national culture in the modern era.